2020
DOI: 10.1080/22221751.2020.1826362
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of diagnostic performance of serology tests for COVID-19: impact of assay design and post-symptom-onset intervals

Abstract: Serology detection is recognized for its sensitivity in convalescent patients with COVID-19, in comparison with nucleic acid amplification tests (NAATs). This article aimed to evaluate the diagnostic accuracy of serologic methods for COVID-19 based on assay design and post-symptom-onset intervals. Two authors independently searched PubMed, Cochrane library, Ovid, EBSCO for case–control, longitudinal and cohort studies that determined the diagnostic accuracy of serology tests in comparison with NAATs in COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 50 publications
8
59
2
Order By: Relevance
“…Serum antibodies are also more stable than viral RNA collected via swabbing. In addition, IgM is potentially useful for detecting recent infection for most cases because it usually becomes undetectable weeks following infection, and the presence of the IgG antibody often indicates a past infection because it generally does not appear until 7 to 10 days after the onset of infection and may last for months or years after infection [ 12 , 13 , 14 ]. Accordingly, serological tests offer some advantages to complement PCR-based diagnosis and screening for COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…Serum antibodies are also more stable than viral RNA collected via swabbing. In addition, IgM is potentially useful for detecting recent infection for most cases because it usually becomes undetectable weeks following infection, and the presence of the IgG antibody often indicates a past infection because it generally does not appear until 7 to 10 days after the onset of infection and may last for months or years after infection [ 12 , 13 , 14 ]. Accordingly, serological tests offer some advantages to complement PCR-based diagnosis and screening for COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…We could previously show that the sensitivity of SARS-CoV-2 antibody tests can drop below 90%, especially when non-hospitalized patients are included (4). In the meantime, suboptimal sensitivities of SARS-CoV-2 antibody tests have been described in numerous subsequent publications (4, 7, 12, 32). Thus, an orthogonal test strategy with a certain further loss of sensitivity does not seem appropriate for seroprevalence studies, especially considering the dynamic development of infection rates we are facing.…”
Section: Discussionmentioning
confidence: 99%
“…According to the recent meta-analysis of diagnostic performance of serology tests for COVID-19, the pooled sensitivity of Immunoglobin G (IgG), Immunoglobin M (IgM) and combined IgM-IgG tests in confirmed COVID-19 patients was 0.76 (95% CI: 0.65–0.86), 0.69 (95% CI: 0.59–0.78) and 0.78 (95% CI: 0.70–0.85), respectively. Thus, negative serological results alone cannot exclude the diagnosis of COVID-19 [ 55 ].…”
Section: Detection Of Covid-19 In Alternative Samples/sitesmentioning
confidence: 99%
“…It was further demonstrated that serology tests had the lowest sensitivity at 0–7 days after symptom onset, and the highest sensitivity (more than 85%) at >14 days, suggesting that serological tests might be useful for diagnosis purposes at later stages of disease. The specificity of IgG, IgM and combined IgM-IgG tests was 0.98 (95% CI: 0.96–0.99), 0.95 (95% CI: 0.91–0.98) and 0.97 (95% CI: 0.93–0.99), respectively [ 55 ]. In another meta-analysis, SARS-CoV-2 seropositivity rate was estimated to be 61.2% (95% CI: 53.4–69.0%) for IgM, 58.8% (95% CI: 49.6–68.0%) for IgG and 62.1% (52.7–71.4%) for IgM-IgG joint detection in confirmed patients.…”
Section: Detection Of Covid-19 In Alternative Samples/sitesmentioning
confidence: 99%